Beyond Religious Right and Secular Left Rhetoric The Road to Compromise - Fry, Karin; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book covers arguments made by various sides of the political-religious divide from the past 30 years, showing what the actual differences are between these groups. By stressing the typically ignored similarities, the book better informs partisans and the public to move debate forward.
Keywords: Science; Science; Science, general